2019
DOI: 10.1108/jocm-10-2018-0280
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of sensemaking through socio-material practices

Abstract: Purpose The purpose of this paper is to increase understanding of how sensemaking occurs as a holistic, processual phenomenon during an organisational change. Design/methodology/approach A longitudinal, qualitative case study was conducted by analysing video-recorded meetings among the staff of two recently merged surgical departments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Weiser's (2021) study of strategic change in a software company showed that sensemaking is a multi-modal process, combining discursive practices such as sensegiving with "substantive actions," such as making modifications to the organizational structure. Jansson, Lunkka, Suhonen, Meriläinen, and Wiik (2019) also emphasize the interplay of material and discursive practices in the formation of collective sense, using video recordings to identify how staff in a recently merged surgical unit developed their working practices, including the replaying of video recordings to facilitate sensemaking. Finally, Nissi and Pälli (2020) advanced our understanding of how shared sensemaking is facilitated by multimodal artefacts.…”
Section: Language and Social Practice: Patterns Of Language Use In So...mentioning
confidence: 99%
See 1 more Smart Citation
“…Weiser's (2021) study of strategic change in a software company showed that sensemaking is a multi-modal process, combining discursive practices such as sensegiving with "substantive actions," such as making modifications to the organizational structure. Jansson, Lunkka, Suhonen, Meriläinen, and Wiik (2019) also emphasize the interplay of material and discursive practices in the formation of collective sense, using video recordings to identify how staff in a recently merged surgical unit developed their working practices, including the replaying of video recordings to facilitate sensemaking. Finally, Nissi and Pälli (2020) advanced our understanding of how shared sensemaking is facilitated by multimodal artefacts.…”
Section: Language and Social Practice: Patterns Of Language Use In So...mentioning
confidence: 99%
“…Jansson et al (2019) also emphasize the interplay of material and discursive practices in the formation of collective sense, using video recordings to identify how staff in a recently merged surgical unit developed their working practices, including the replaying of video recordings to facilitate sensemaking. Finally, Nissi and Pälli (2020) advanced our understanding of how shared sensemaking is facilitated by multimodal artefacts.…”
mentioning
confidence: 99%